Eco-friendly green roof from biodegradable substrate for stormwater quality improvement - N I Z, Mohd Azam; Noor Suraya, Romali; Abdul Syukor, Abd Razak (IOP Publishing Ltd., 2024)
Currently, there is a significant surge of interest in green roof technology for construction buildings due to its numerous environmental benefits, such as stormwater management, energy efficiency, and enhanced urban biodiversity. However, the issue of potential pollutant release from green roof substrates into runoff water, causing water pollution, needs to be addressed. To tackle this concern, a lab-scale green roof model was assessed, utilizing a biodegradable substrate made from banana peels and eggshell waste (organic fertilizer). Three models were tested: a conventional green roof (control), a green roof with chemical fertilizer, and a green roof with organic fertilizer. Various water quality parameters, including pH, total suspended solids (TSS), nitrogen, phosphorus, and potassium (NPK), and chemical oxygen demand (COD), were evaluated. The results demonstrated the effectiveness of organic fertilizer in reducing TSS and COD levels, where the eco-friendly green roof with biodegradable substrate exhibited an impressive performance, achieving a higher COD removal percentage (78%) compared to the green roof with chemical fertilizer (50%). The utilization of organic fertilizer led to an enhancement in the quality of stormwater runoff, resulting in NPK removal percentages ranging from 17% to 25%. Additionally, the organic fertilizer fostered healthier vegetation growth, leading to a greater number of leaves compared to the chemical fertilizer. These findings highlight the potential of eco-friendly green roofs as a sustainable and effective tool for stormwater management, provided suitable substrate materials are employed.